Attitudes to Evidence‐Based Interventions and Individual Readiness to Change in Maternity and Child Health Care: A Cross‐Sectional Study Among Midwives and Public Health Nurses - Olavesen, Ellen Solstad; Helseth, Sølvi; Wentzel‐Larsen, Tore; Haga, Silje Marie; Sundrehagen, Thea Grossmann; Valla, Lisbeth; Drozd, Filip (Worldviews on evidence-based nursing, 2025)
ABSTRACT Background Integrating evidence‐based interventions in services by midwives and public health nurses (PHNs) has the potential to improve public health. Attitudes and individual readiness to change can influence the implementation of evidence‐based interventions, but there is limited research in community nursing and maternity and child health care services (MCHCs). Aims To examine attitudes toward evidence‐based practice and readiness to change in midwives and PHNs in MCHCs before implementing the “Mamma Mia” intervention (an evidence‐based intervention to improve maternal mental health). Methods A survey‐based, multisite cross‐sectional study following the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) guideline. Data were collected from 190 midwives and PHNs from 42 MCHCs across 33 municipalities in Norway (2021–2022). Six subscales of the Evidence‐Based Practice Attitude Scale (EBPAS) assessed attitudes toward evidence‐based practice, and the Brief Individual Readiness for Change Scale (BIRCS) measured individual readiness. Descriptive and inferential statistics using frequency tables, Pearson correlation coefficient, and linear regression were used for data analysis. Open‐ended responses were analyzed using content analysis. Results Sixty‐five midwives and 125 PHNs completed the baseline survey (mean age 46.8, all female). Mean EBPAS subscales scores were 2.99 to 3.58 (SD = 0.46–0.77) mean BIRCS score was 3.16 (SD = 0.49) (possible range 0–4). Scores were slightly higher than typically reported in clinical settings, with no significant differences based on demographics (all p‐values ≥ 0.166). EBPAS subscores and the BIRCS score showed a moderate positive association. The most frequently reported positive factors influencing readiness were “enhanced care and positive gain” (42.6%), “organizational support” (26.3%), and “receiving training and implementation support” (23.2%). Negative factors included “time constraints and workload” (58.4%), and “research participation and implementation demands” (27.9%). Linking Evidence to Action Midwives and PHNs showed positive attitudes toward EBP and a high degree of individual readiness. Our findings align with previous research highlighting barriers such as time constraints and workload, offering insights to inform strategies for more effective EBP adoption and implementation. These results can guide nurse managers, administrators, policymakers, professional associations, implementers, and intervention developers in enhancing EBP integration into practice.